Changes in circulating miRNAs in healthy overweight and obese subjects: Effect of diet composition and weight loss. Issue 1 (February 2019) - Giardina, S.; Hernández-Alonso, P.; Díaz-López, A.; Salas-Huetos, A.; Salas-Salvadó, J.; Bulló, M.
Summary: Background: MicroRNAs (miRNAs) are small non-coding RNA molecules that can play an important role in several chronic metabolic conditions, including obesity. However, to date little is known about how they are regulated. Weight loss induced by surgical procedures has been effective at modulating specific circulating miRNAs, but the effect of energy-restricted diets with different macronutrient compositions on circulating miRNAs is not well understood. The objective of the present analysis was to explore the effect of three energy-restricted diets of different macronutrient composition and carbohydrate quality on plasma miRNA levels. Methods: The GLYNDIET study is a 6-month, parallel, randomized clinical trial conducted on overweight and obese subjects who were randomized to one of three different dietary intervention groups: i) a moderate-carbohydrate and low glycemic index diet (LGI), ii) a moderate-carbohydrate and high glycemic index diet (HGI), and iii) a low-fat and high glycemic index diet (LF). We assessed the genome-wide circulating miRNA profile in a subsample of eight randomly selected participants. A total of 8 miRNAs (miR-411, miR-432, miR-99b, miR-340, miR-423, miR-361, let-7c) were differently quantified according to diet intervention, and were therefore longitudinally validated in 103 participants before and after the energy-restricted diets. Results: Circulating miR-361 levels were lower in the LGI group than in the HGI group, even after adjusting for differences in weight loss. The intra-group analyses demonstrated a significant down-regulation of all miRNAs screened in our study subjects after the LGI intervention. Similarly, miR-139 and miR-340 were down-regulated after the HGI intervention, while miR-139, miR-432 and miR-423 were down-regulated after the low-fat diet. Changes in circulating miR-139 and let-7c were significantly associated with changes in lipid profile and insulin resistance. Conclusion: An energy-restricted low-glycemic index diet down-regulates circulating miRNA-361 more than an energy-restricted high-glycemic index, regardless of the magnitude of the weight loss.